Happiness and sadness recognition system: preliminary results with an Intel RealSense 3D Sensor - Silva, Vinicius Corrêa Alves (2017)
Systems and devices that can recognize human affects have been in development for a considerable time. Facial features are usually extracted by using video data or a Microsoft Kinect sensor. The present paper proposes an emotion recognition system that uses the recent Intel RealSense 3D sensor, whose reliability and validity in the field of emotion recognition has not yet been studied. This preliminary work focus on happiness and sadness. The system extracts the user’s facial Action Units and head motion data. Then, it uses a Support Vector Machine to automatically classify the emotion expressed by the user. The results point out the adequacy of Intel RealSense for facial features extraction in emotion recognition systems as well as the importance of determining head motion when recognizing sadness.